Performance Evaluation of DG Interconnected Radial Distribution System - Gaurav Chauhan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The distribution system has become very complex entity due to increase in power system utilities, so it is very difficult task to improve the voltage profile and to maintain the quality of power of such complex system. Distribution generation (DG) can play major role to enhance the power quality of the system and also improves the reliability of the system. DGs act as an active distribution system and form the link between high voltage transmission line and low voltage utility. This helps in reducing the active power loss of the system. This paper presents optimizing techniques for DG model in terms of operating point, size and location to minimize the active power loss of overall system. For the proposed objective functions the variation in power loss can be observed with respect to DG current injection. The load characteristics have been taken into consideration to develop the proposed techniques and the system has been treated as constant current model. The proposed system has been simulated and verified by MATLAB software for RDS (radial distribution system).